2021
DOI: 10.1021/acscatal.1c03039
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Selective Synthesis of Alkylcyclopentenyl Cations in Zeolites and Spectroscopic Distinction of Constitutional Isomers

Abstract: Alkylcyclopentenyl cations belong to the long-lived intermediates that make up the “hydrocarbon pool” during the catalytic conversion of methanol on zeolites, and recent works show that such cations contribute to olefin and aromatics formation. From liquid phase chemistry, two types of alkylcyclopentenyl cations are known and distinguished by the substituent at the central carbon (C-2) of the allylic system: a more stable type with a methyl group at the C-2 and a less stable type with hydrogen at the C-2. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 93 publications
1
36
0
Order By: Relevance
“…37 The extent to which olefin and aromatic cycle contribute to the overall rate of olefin production is still under debate and likely varies for different catalysts such as H-ZSM-5, 33,[40][41][42] H-BEA, 10,13,[43][44][45] H-SAPO-34 19,46,47 and H-SSZ-13. [48][49][50] While some experimental observations involve cyclopentenyl cations, 42,[51][52][53][54][55][56] all detailed mechanistic proposals for the aromatic cycle start from aromatic polymethylbenzenes. Two mechanistic variants have been proposed for the production of olefins via the aromatic cycle, the side-chain and the paring mechanism (see Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…37 The extent to which olefin and aromatic cycle contribute to the overall rate of olefin production is still under debate and likely varies for different catalysts such as H-ZSM-5, 33,[40][41][42] H-BEA, 10,13,[43][44][45] H-SAPO-34 19,46,47 and H-SSZ-13. [48][49][50] While some experimental observations involve cyclopentenyl cations, 42,[51][52][53][54][55][56] all detailed mechanistic proposals for the aromatic cycle start from aromatic polymethylbenzenes. Two mechanistic variants have been proposed for the production of olefins via the aromatic cycle, the side-chain and the paring mechanism (see Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Carbocations are also important intermediates in other zeolitecatalyzed reactions, such as poly-ethylated benzenium ions in the ethanol to olefins (ETO) reaction as the ''sister-reaction'' of MTO, 42,46,75,149,314 cyclic carbenium ions in 1-ethylcyclohexene isomerization, 213 alkylated naphthyl carbenium ions in the conversion of ethene to propene, 315 acylium ion in DME/ methanol carbonylation 102 and Friedel-Crafts acylation, 316,317 and alkylated phenyl carbenium ions in alkylaromatic transalkylation. 117,276,[318][319][320][321][322] Chowdhury et al 149 employed spectroscopic approaches to validate the reaction and deactivation mechanism of the ETO process in H-ZSM-5, where alkyl side chain carbenium ions, alkylated phenyl carbenium ions, and poly-arenium ions were detected as the intermediates to produce alkenes by operando UV-Vis diffuse reflectance spectroscopy.…”
Section: Carbocation In Other Reactionsmentioning
confidence: 99%
“…117,276,[318][319][320][321][322] Chowdhury et al 149 employed spectroscopic approaches to validate the reaction and deactivation mechanism of the ETO process in H-ZSM-5, where alkyl side chain carbenium ions, alkylated phenyl carbenium ions, and poly-arenium ions were detected as the intermediates to produce alkenes by operando UV-Vis diffuse reflectance spectroscopy. Hernandez et al 213 explained the mechanism of 1-ethylcyclohexene isomerization in the EUO zeolite, where the ethylcyclohexenium ion would be formed by the protonation of 1-ethylcyclohexene with BAS, and the subsequent ring contraction-expansion reactions would involve a PCP + -like transition state with the character of carbonium ions. Moreover, the insightfully theoretical calculations indicated that the different stabilizations of the ethylcyclohexenium ion by the intersection, 12MR pockets and 10MR channels would result different catalytic activity from the free energy surfaces.…”
Section: Carbocation In Other Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary of results from Hernandez et al Experimental IR data are consistent with methyl-substituted form in H-MOR, H-substituted form in H-ZSM-22, and both methyl- and H-substituted forms in H-ZSM-5, while DFT-computed free energies predict that the methyl form is the most stable in all cases.…”
Section: Introductionmentioning
confidence: 99%